Dispersive optical solitons and conservation laws of Radhakrishnan–Kundu–Lakshmanan equation with dual–power law nonlinearity - Ahmed H. Arnous; Anjan Biswas; Abdul H. Kara; Yakup Yıldırım; Luminita Moraru; Simona Moldovanu; Puiu Lucian Georgescu; Abdulah A. Alghamdi (Heliyon, 2023)
The current paper implements three elegant approaches to recover a complete spectrum of optical solitons to the Radhakrishnan–Kundu–Lakshmanan equation with dual–power law of nonlinear refractive index. The conservation laws are also recovered by the usage of multipliers approach. The parameter constraints for the existence of such solitons are also enumerated. The numerical simulations of the recovered soliton solutions are also presented.